Effect of urea supplementation in diet based on barley grain or corn silage on performance, digestion, rumen fermentation and microbial protein synthesis in Holstein bull calves - KAZEMI-BONCHENARI, M; SALEM, A Z M; GHASEMI, E (The Indian Journal of Animal Sciences, 2016)
This study was aimed to evaluate the effect of non-protein nitrogen source of urea with barley grain (BG) or corn silage (CS) based diet in Holstein bull calves. Nutrient digestibility, rumen fermentation activities, microbial nitrogen yield (MN) and blood metabolites were determined. Holstein bull calves (14), weighing 126 ± 4.2 kg were allocated in 2 different diets based on BG or CS for 9 weeks. Diets were based on rolled barley grain (BG) and on finely chopped corn silage (CS). Both diets were supplemented with 7.5 g/kg urea on DM basis. Intake and performance of animal did not differ between diets, whereas digestibility of neutral detergent fiber (NDF) decreased in BG diet. Ruminal concentration of propionate and blood glucose concentration increased in BG calves, whereas ruminal pH and acetate concentration increased in CS fed calves. The ruminal NH3-N was increased in CS diet, while excretions of allantoin, purine derivatives and estimated MN yield through urine were greater in BG diet vs. CS diet. In conclusion, the results suggested that increased urinary PD excretion and consequently increased estimated MN yield value for BG diet presented more potential for this diet to be synchronized with urea in calves’ rumen digestion.